1996
DOI: 10.1002/(sici)1521-186x(1996)17:6<436::aid-bem2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart diseases: Assessment of risk associated with work exposure to ultralow-frequency magnetic fields

Abstract: The present analysis was stimulated by previous findings on the possible influence of natural ultralow‐frequency (ULF; 0.001–10 Hz) geomagnetic field variations on the cardiovascular system and indications of an effect of man‐made ULF magnetic fields on the rate of myocardial infarction. In the present study, we considered the occupational health hazards of the strongest ULF magnetic fields in densely populated urban areas. Measurements of ULF magnetic field fluctuations produced by trains powered by DC electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Recent studies indicate that exposure to electromagnetic fields may have an influence on coronary heart disease in railway workers (Ptitsyna et al 1996). As biogenic magnetite provides a possible mechanism for interactions of weak magnetic fields with the human brain (Kirschvink 1992, Dobson & St. Pierre 1996 it is important to examine its presence and understand its role in other human organs as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that exposure to electromagnetic fields may have an influence on coronary heart disease in railway workers (Ptitsyna et al 1996). As biogenic magnetite provides a possible mechanism for interactions of weak magnetic fields with the human brain (Kirschvink 1992, Dobson & St. Pierre 1996 it is important to examine its presence and understand its role in other human organs as well.…”
Section: Discussionmentioning
confidence: 99%
“…The most important results are not only those concerning cardiovascular diseases and diseases of the nervous system, especially strokes, myocardial infarctions, and traffic accidents (Villoresi et al 1994a, b;Ptitsyna et al 1996Ptitsyna et al , 1998Dorman et al 1999) but also those concerning human physiological parameters variations such as heart rate and arterial systolic and diastolic pressure (Dimitrova 2008;Dimitrova et al 2009;Papailiou et al 2011a). More specifically, in Dimitrova (2008), a group of 86 volunteers was examined during periods of high solar and geomagnetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that during FDs, the average number of traffic accidents and cardiovascular diseases, as myocardial infractions and brain strokes, was higher. These results were in agreement with other studies (Villoresi et al 1994a, b;Ptitsyna et al 1996). Moreover, train accidents (caused by man-related factors) can also be influenced by FDs events (Dorman et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained in the laboratory regarding the blood’s sensitivity to solar and GMA strengthen this new field, while the most important results concern diseases of the cardiovascular and nervous systems (Dorman et al 2001 ). It is being argued that Forbush decreases (FDs) of CRI are representative of the relationship between geomagnetic disturbances and health parameters, e.g., ischemic attacks, myocardial infarction, and traffic accidents (Villoresi et al 1994a ; b ; 1998 ; Ptitsyna et al 1996 ; Dorman et al 1999 ). Moreover, during the development of a geomagnetic disturbance, the most important and statistically significant results are observed in the decrease phase of the FDs of CRI.…”
Section: Introductionmentioning
confidence: 99%